Clinical Evaluation of the Levels of CEA,CA15-3 and AlphaFeto Protein in Malignant and Benign Pleural Effusion - Marrow, Zina Anwer Salloum; Al-Kassir, Abdul Hammed A.; Al-Sakkal, Nahla Majeed Tawfiq; Khadduri, Julian Dulayl (AL-Kindy College Medical Journal, 2008)
Background: Pleural effusion is a common clinical problem. Objective: The aim of the study was to evaluate the diagnostic utility of Carcino embryonic antigen (CEA), CA 15- 3, and alpha-feto protein ( AFP ) as a tumor markers in serum and pleural effusion and evaluate the value of combining them as a diagnostic tools that are complementary to cytology in the diagnosis of malignancies . Methods: Forty patients (18 malignant and 22 benign pleural effusion) were included in this study .The serum and effusion levels of CEA, CA 15 – 3 and AFP were measured using immunoradiometric assay Results: from the 40 effusions studied 26 were exudates and 14 were transudates. The level of pleural effusions of CEA, CA 15 – 3 and AFP were increased above the cutoffs in 72.5%, 94.4 % and 5.5 % of tested samples with malignancies respectively. A direct strong significant correlation between serum and pleural fluid CEA, CA 15 – 3 and AFP was noted. Conclusion: Pleural effusion CEA is the most accurate marker for the diagnostic separation of malignant and benign. The combination of both CEA, CA 15 – 3 improves the sensitivity by up to 11 %. AFP has no role in the process